Dutch Arcadia: Amsterdam and villa culture (OverHolland, 2017)
The Dutch buitenplaats, literally ‘country-place’, is commonly used to describe a complex of house and gardens. The word ‘villa’ is very rare in contemporary Dutch descriptions, and is used only very sporadically in historical studies, while the Dutch ‘buitenplaats’ is much more common. The crucial relation between the city and its hinterland has strong etymological roots: even today, the Dutch buiten simply means ‘outside’ or ‘countryside’, but het buiten signifies a country place or country house. It is a reminder of the historical importance of out-of-town life in the heavily urbanized Dutch landscape that was created from the late sixteenth century. While the classical age of the Dutch country mansion, from the mid 1640s to 1672 has been studied extensively, the age when Dutch villa culture reached its peak in the early eighteenth century, has been dealt with superficially. The Dutch buitenplaats as the locus of nineteenth century ‘culture of notables’ and the shaping of an aristocratic lifestyle, has recently been rediscovered. Links with the developments of the preceding century were not investigated, however. Over the last decades scholars from different fields, such as economic, social, urban and landscape history, using wide-ranging archival material, have been able to reconstruct parts of this now lost culture. Dutch villa culture, once undeniably present in the landscape outside the cities, and by its sheer quantity impressive even on a European scale, has survived mainly on paper and canvas, and through the names of streets or neighbourhoods of nineteenth and twentieth-century expansions of Dutch cities that almost completely replaced the various villa landscapes that flowered in the early eighteenth century. Frankendael was once one of fifty country houses in the polder of Watergraafsmeer. Today, it is the only one that has survived in the area that was annexed in 1921 and became a suburb of Amsterdam.